Phyllanthus spp. Induces Selective Growth Inhibition of PC-3 and MeWo Human Cancer Cells through Modulation of Cell Cycle and Induction of Apoptosis - Yin-Quan Tang; Indu Bala Jaganath; Shamala Devi Sekaran (2010)
Background Phyllanthus is a traditional medicinal plant that has been used in the treatment of many diseases including hepatitis and diabetes. The main aim of the present work was to investigate the potential cytotoxic effects of aqueous and methanolic extracts of four Phyllanthus species (P.amarus, P.niruri, P.urinaria and P.watsonii) against skin melanoma and prostate cancer cells. Methodology/Principal Findings Phyllanthus plant appears to possess cytotoxic properties with half-maximal inhibitory concentration (IC50) values of 150–300 µg/ml for aqueous extract and 50–150 µg/ml for methanolic extract that were determined using the MTS reduction assay. In comparison, the plant extracts did not show any significant cytotoxicity on normal human skin (CCD-1127Sk) and prostate (RWPE-1) cells. The extracts appeared to act by causing the formation of a clear “ladder” fragmentation of apoptotic DNA on agarose gel, displayed TUNEL-positive cells with an elevation of caspase-3 and -7 activities. The Lactate Dehydrogenase (LDH) level was lower than 15% in Phyllanthus treated-cancer cells. These indicate that Phyllanthus extracts have the ability to induce apoptosis with minimal necrotic effects. Furthermore, cell cycle analysis revealed that Phyllanthus induced a Go/G1-phase arrest on PC-3 cells and a S-phase arrest on MeWo cells and these were accompanied by accumulation of cells in the Sub-G1 (apoptosis) phase. The cytotoxic properties may be due to the presence of polyphenol compounds such as ellagitannins, gallotannins, flavonoids and phenolic acids found both in the water and methanol extract of the plants. Conclusions/Significance Phyllanthus plant exerts its growth inhibition effect in a selective manner towards cancer cells through the modulation of cell cycle and induction of apoptosis via caspases activation in melanoma and prostate cancer cells. Hence, Phyllanthus may be sourced for the development of a potent apoptosis-inducing anticancer agent.